Impact of an information video before colonoscopy on patient satisfaction and anxiety - Mahmut Arabul,; Altay KANDEMİR,; Mustafa Çelik,; Emrah Alper,; Zehra Akpınar,; Fatih Aslan,; Sezgin VATANSEVER,; Belkıs Ünsal, (Turkish Journal of Gastroenterology, 2019)
-